Кон André Kukla, Social Constructivism and the Philosophy of Science: Për André Kukla, Social Constructivism and the Philosophy of Science - Ivanovska, Marija; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2002)
Author(s): Marija Ivanovska | Марија Ивановска Title (Macedonian): Кон André Kukla, Social Constructivism and the Philosophy of Science Title (Albanian): Për André Kukla, Social Constructivism and the Philosophy of Science Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 3 (Summer 2002) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 197-198 Page Count: 2 Citation (Macedonian): Марија Ивановска, „Кон André Kukla, Social Constructivism and the Philosophy of Science“, Идентитети: списание за политика, род и култура, т. 1, бр. 3 (лето 2002): 197-198. Citation (Albanian): Marija Ivanovska, „Për André Kukla, Social Constructivism and the Philosophy of Science“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 3 (Summer 2002): 197-198.